Faces of Terrorism in the Age of Globalization: Terrorism from Above and Below - Jalata, Asafa (2008)
This paper explains how the intensification of globalization as the modern world system with its ideological intensity of racism and religious extremism and its concomitant advancement in technology and organizational skills has increased the danger of all forms of terrorism. In this world system, the contestation over economic resources and power and the resistance to domination and repression or religious and ideological extremism have increased the occurrence of terrorism from above (i.e. state actors) and from below (i.e. non-state actors). We cannot adequately grasp the essence and characteristics of modern terrorism without understanding the larger cultural, social, economic, and political contexts in which it takes place. Since terrorism has been conceptualized, defined, and theorized by those who have contradictory interests and objectives and since the subject matter of terrorism is complex, difficult, and elusive, there is a wide gap in establishing a common understanding among the scholars of terrorism studies. Most experts on the subject look at this issue from a narrow perspective by ignoring the reality that terrorism is a “social cancer” for all human groups affected by it. First, this paper defines the concept of terrorism in relation to different forms of terrorism, and explains how it has increased with the intensification of globalization. Second, taking the events of 9/11 and the case of Ethiopian state terrorism, the piece explores the general impacts of all forms of terrorism